Adoption of Digital Therapeutics in Europe - Fassbender A; Donde S; Silva M; Friganovic A; Stievano A; Costa E; Winders T; van Vugt J (Therapeutics and Clinical Risk Management)
Amelie Fassbender,1 Shaantanu Donde,2 Mitchell Silva,3 Adriano Friganovic,4– 6 Alessandro Stievano,7 Elisio Costa,8 Tonya Winders,9 Joris van Vugt10 1Medical Affairs DM, Viatris, Hoeilaart, Belgium; 2Medical Affairs, DM&JANZ, Viatris, Hatfield, London, UK; 3Executive Management, Esperity, Brussel, Belgium; 4University Hospital Centre, Zagreb, Croatia; 5University of Applied Health Sciences, Zagreb, Croatia; 6Faculty of Health Studies, University of Rijeka, Rijeka, Croatia; 7Department of Clinical and Experimental Medicine, University of Messina, Messina, Italy; 8Faculty of Pharmacy, CINTESIS@RISE, Competence Center on Active and Healthy Ageing (Porto4Ageing), University of Porto, Porto, Portugal; 9Board of Directors, Global Allergy & Airways Patient Platform, Vienna, Austria; 10Medical Affairs, DM&JANZ, Viatris, Amstelveen, the NetherlandsCorrespondence: Amelie Fassbender, Email amelie.fassbender@viatris.comAbstract: Digital therapeutics (DTx) are an emerging medical therapy comprising evidence-based interventions that are regulatory approved for patient use, or are under development, for a variety of medical conditions, including hypertension, cancer, substance use disorders and mental disorders. DTx have significant potential to reduce the overall burden on healthcare systems and offer potential economic benefits. There is currently no specific legal regulation on DTx in the EU. Although European countries have similar approaches to digital health solutions, the adoption of DTx varies across the continent. The aim of this narrative review is to discuss the levels of adoption of DTx in Europe, and to explore possible strategies to improve adoption, with the goal of higher rates of adoption, and more consistent use of DTx across the continent. The article discusses the regulatory and reimbursement landscape across Europe; validation requirements for DTx, and the importance of co-design and an ecosystem-centric approach in the development of DTx. Also considered are drivers of adoption and prescription practices for DTx, as well as patient perspectives on these therapeutics. The article explores potential factors that may contribute to low rates of DTx adoption in Europe, including lack of harmonisation in regulatory requirements and reimbursement; sociodemographic factors; health status; ethical concerns; challenges surrounding the use and validation of AI; knowledge and awareness among healthcare professionals (HCPs) and patients, and data standards and interoperability. Efforts to improve rates of access to DTx and adoption of these therapeutics across Europe are described. Finally, a framework for improved uptake of DTx in Europe is proposed.Keywords: digital health, regulatory, reimbursement, healthcare professionals, health inequalities